2020
DOI: 10.1016/j.ibusrev.2020.101713
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to work for multinational enterprises from emerging countries: The case of Chinese multinational enterprises in the Netherlands

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 171 publications
(256 reference statements)
0
7
0
Order By: Relevance
“…Scholars are not consentient about the influencers of place perceptions (Mikuli c et al, 2016;Richards, 2017;Zhang et al, 2020). The distinctive strategies thereby face a problem concerning specific and actionable commercial tactics; this phenomenon culminates in ineffective place branding (Julier, 2005).…”
Section: Place Branding and Brand Heritagementioning
confidence: 99%
“…Scholars are not consentient about the influencers of place perceptions (Mikuli c et al, 2016;Richards, 2017;Zhang et al, 2020). The distinctive strategies thereby face a problem concerning specific and actionable commercial tactics; this phenomenon culminates in ineffective place branding (Julier, 2005).…”
Section: Place Branding and Brand Heritagementioning
confidence: 99%
“…Energy and/or environment-related technological progress are widely accepted as solutions to reducing the energy-environment-economy conflict (Acemoglu et al, 2012;Acemoglu et al, 2018;Song and Wang, 2018). Energy-and environment-saving technologies present opportunities for emerging economies to catch up or even leapfrog developed countries, ultimately achieving sustainable development (Zhang et al, 2020;Wang and Wei, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with the international business studies indicating that there is a relationship between firm and country characteristics (e.g. Sharma, 2011; Zhang et al ., 2019, 2020). The indirect effects presented in the low part of Table 6 indicate that Positive News and Negative news both were significantly related to Attractiveness through the three dimensions of CI.…”
Section: Resultsmentioning
confidence: 99%
“…A country might be regarded as a broader category of firm and means that a CI may also be perceived as an information cue that influences firm attractiveness. A recent study found that CI indeed does have a significant impact on firms’ attractiveness (Zhang et al ., 2020). Therefore, we expected that, besides the direct effect, media salience may have an indirect effect on firm attractiveness through CI.…”
Section: Literature Review and Hypothesismentioning
confidence: 99%